IDENTIFICATION AND VERIFICATION OF HEREDITARY SPHEROCYTOSIS BY MEANS OF LABORATORY DIAGNOSIS - Yu. A. Prokhorova; E. E. Zueva; N. E. Sokolova; G. N. Salogub; V. I. Golubeva (Union of pediatricians of Russia, 2014)
Aim. Hereditary spherocytosis (HS) is the most commonly encountered erythrocyte membranopathy. Frequency of occurrence of the disease makes one case per 2000−5000 newborns. Hereditary spherocytosis often causes a complex of clinical signs, including hemolytic crises in patients. At the same time many patients have asymptomatic HS. Differential diagnosis of HS is quite complex and in modern workload conditions the clinical doctors need a simpler diagnostics procedure. Patients and methods. Participants included 13 adults with verified hereditary spheroсytosis and 42 children with identified hereditary spherocytosis, 311 adults without hematological disorders, 42 children without hematological disorders. Verification of hereditary spherocytosis diagnosis was carried out using flow cytometry test (eosine-5 maleimid-binding), Deich`s method of determination of erythrocyte osmotic resistance and Sodium Dodecyl Sulfate-Poly Acrylamide Gel Electrophoresis. In this study we have assessed diagnostic value of hematological parameters provided by the hematological analyzer Beckman Coulter Cellular Analysis System DxH800 for identifying the degree of erythropoiesis disorder in patients with hereditary spherocytosis at the stage of reticulocytes maturation. According to our data, the ratio RET/IRF and calculated parameter MCV-MSCV can be used as the screening tests for hereditary spherocytosis. Results. Evaluation of the erythrocytes and reticulocytes parameters at the hematological analyzer identified the significant difference in estimate index MCV-MSCV (p < 0,0001, sensitivity 100%, specificity 100%, area under the ROC-curve 1,0) and RET/IRF (p < 0,0001, sensitivity 96,3%, specificity 94,1, area under the ROC-curve 0,97) between group of patients with HS and control group. We also evaluated the usability of eosine-5 maleimide binding in flow cytometry for verification of this membranopathy. For unify the test results we offer to use estimate indicator S (sample`s MFI / control`s mean MFI), cut level for positive cases of hereditary spherocytosis S < 0,84 (p = 0,0001, sensitivity 98,2%, specificity 99,2%, area under the ROC-curve 0,99). Conclusion. We recommend the hematological analyzer evaluation as the screening option for the identification of HS in patients and determine the estimated parameters for the values of the patients MCV-MSCV and RET/IRF. The most informative verifying test to prove hereditary spherocytosis is the flow cytometry test using eosine-5 maleimid. It is the laboratory test that proves a high degree of sensitivity and specificity for hereditary spherocytosis. Sodium Dodecyl Sulfate-PolyAcrylamide Gel Electrophoresis of red blood cells membranes proteins is useful for specify molecular deficiency in each hereditary spherocytosis case.